2013
DOI: 10.4212/cjhp.v66i3.1253
|View full text |Cite
|
Sign up to set email alerts
|

Compatibility and Stability of Morphine Sulphate and Naloxone Hydrochloride in 0.9% Sodium Chloride for Injection

Abstract: Background: Naloxone may be administered in conjunction with morphine to reduce the risk of opioid-induced pruritis. Combining these drugs for coadministration may be beneficial, but little is known about their physical compatibility and stability in combined solutions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…The MINI-BAG Plus Container System and VIAL-MATE Adaptor have widespread utility across a range of different drugs and therapeutic areas. They are used for the administration not only of drugs that require reconstitution prior to use, 16 , 17 like cefiderocol and other antibiotics, but also ready-to-use products, 18 which can offer favorable safety, reduced waste and, in some cases, economic advantages, and may have particular applications for antimicrobial use in the outpatient setting. The results from this small study support the use of these established systems but should not be extrapolated beyond cefiderocol; the compatibility of other products should be confirmed on an individual basis.…”
Section: Conclusion and Relevancementioning
confidence: 99%
“…The MINI-BAG Plus Container System and VIAL-MATE Adaptor have widespread utility across a range of different drugs and therapeutic areas. They are used for the administration not only of drugs that require reconstitution prior to use, 16 , 17 like cefiderocol and other antibiotics, but also ready-to-use products, 18 which can offer favorable safety, reduced waste and, in some cases, economic advantages, and may have particular applications for antimicrobial use in the outpatient setting. The results from this small study support the use of these established systems but should not be extrapolated beyond cefiderocol; the compatibility of other products should be confirmed on an individual basis.…”
Section: Conclusion and Relevancementioning
confidence: 99%
“…In this study, the infusion samples were visually inspected with the naked eye for the solution colour and clarity each time, and duplicate pH measurements were conducted. 16 All samples from each test were then aliquoted and frozen at −20°C until further analysis. The samples from each bag and bottle were analysed in triplicate (n=3).…”
Section: Stability Study Of the Analgesic Solutionsmentioning
confidence: 99%
“…28 C. Kistner and others studied the effect of different concentrations and time periods of NH injections mixed with morphine sulphate prepared in 0.9% sodium chloride solutions. 16 They reported that 1000 µg/mL morphine sulphate and NH at concentrations of 4, 12.5, or 25 µg/mL in a 0.9% sodium chloride solution for injection remained stable for 72 h at room temperature and for 30 days under refrigeration. In this experiment, the quantitative analysis methods of FC with NH were adapted from the published literature on chromatographic analysis methods.…”
Section: Dovepressmentioning
confidence: 99%
“…If one takes alcohol beyond the upper limit in a short period of time, the Central Nervous System (CNS) gets excited first and then inhibits the alcohol intake. The sudden change can cause serious damage of the CNS, the liver, and other human organs [2,3]. Immediate treatments can help the patient to get through smoothly the critical period of the disorder and reduce the occurrence of complications.…”
Section: Introductionmentioning
confidence: 99%